2007
DOI: 10.1128/mcb.01298-06
|View full text |Cite
|
Sign up to set email alerts
|

RANK Overexpression in Transgenic Mice with Mouse Mammary Tumor Virus Promoter-Controlled RANK Increases Proliferation and Impairs Alveolar Differentiation in the Mammary Epithelia and Disrupts Lumen Formation in Cultured Epithelial Acini

Abstract: RANK and RANKL, the key regulators of osteoclast differentiation and activation, also play an important role in the control of proliferation and differentiation of mammary epithelial cells during pregnancy. Here, we show that RANK protein expression is strictly regulated in a spatial and temporal manner during mammary gland development. RANK overexpression under the control of the mouse mammary tumor virus (MMTV) promoter in a transgenic mouse model results in increased mammary epithelial cell proliferation du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 50 publications
7
108
0
Order By: Relevance
“…Asterisks represent significant differences (Po0.01) compared with pcDNA3-transfected cells. NFjB blockade promotes senescence of differentiating GICs L Nogueira et al signaling through the NFkB activator receptor activator of NFkB (RANK) not only promotes proliferation but also inhibits the terminal differentiation of mammary epithelial cells (Gonzalez-Suarez et al, 2007). Our data show that maintained NFkB blockade in GICs undergoing differentiation, promotes proliferation arrest, morphological changes (enlarged and flattened shape), polyploidy, increase in phospho-H2AX-containing nuclear foci and induction of b-gal, which are features of cellular senescence.…”
Section: Discussionmentioning
confidence: 52%
“…Asterisks represent significant differences (Po0.01) compared with pcDNA3-transfected cells. NFjB blockade promotes senescence of differentiating GICs L Nogueira et al signaling through the NFkB activator receptor activator of NFkB (RANK) not only promotes proliferation but also inhibits the terminal differentiation of mammary epithelial cells (Gonzalez-Suarez et al, 2007). Our data show that maintained NFkB blockade in GICs undergoing differentiation, promotes proliferation arrest, morphological changes (enlarged and flattened shape), polyploidy, increase in phospho-H2AX-containing nuclear foci and induction of b-gal, which are features of cellular senescence.…”
Section: Discussionmentioning
confidence: 52%
“…This apparent distinction between the ability of RANK activity to promote a transformative phenotype in normal NMuMG, but not in MC3T3-E1 cells, was unexpected, but highly relevant. Gonzalez-Suarez and colleagues (Gonzalez-Suarez et al, 2007) showed that overexpression of RANK in the epithelial cell compartment of the mammary gland led to profound hyperplasia and impaired alveolar differentiation, although overt tumor formation did not occur. Recently, Santini and co-workers (Santini et al, 2011) provided a correlation between breast cancers expressing high levels of RANK and poor patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired mammary gland development of the RANK and RANKL null mice is due to defective proliferation and increased apoptosis of mammary epithelium (2). Conversely, overexpression of RANK or RANKL in the mammary gland leads to increased proliferation of the mammary epithelia (3,4). It has been postulated that paracrine signaling through RANK/RANKL is responsible for the expansion of mammary stem cells observed during pregnancy and luteal cycles (5,6).…”
Section: Introductionmentioning
confidence: 99%